2014
DOI: 10.1002/biot.201300320
|View full text |Cite
|
Sign up to set email alerts
|

The hollow fiber bioreactor as a stroma‐supported, serum‐free ex vivo expansion platform for human umbilical cord blood cells

Abstract: The bone marrow microenvironment plays an integral role in the regulation of hematopoiesis. Residing stromal cells and the extracellular matrix in the bone marrow microenvironment provide biological signals that control hematopoietic stem cell (HSC) function. In this study, we developed a bio-mimetic co-culture platform using the hollow fiber bioreactor (HFBR) for ex vivo expansion of HSCs. We evaluated the efficacy of such a platform in comparison to standard cultures performed on tissue culture polystyrene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…Moreover, in the oncological field, these 3D models can be useful for in vitro production of human hematopoietic cells. Indeed, the HSCs transplantation, a widely used therapy for several hematological malignancies, presents two important limitations: an insufficient number of matching donors and the difficulty of obtaining enough cells [174]. Thus, expanding HSCs, obtained from donors, can be a suitable strategy to overcome these obstacles.…”
Section: D Models For Expanding Normal Hsc a Tool For Clinical Therapymentioning
confidence: 99%
“…Moreover, in the oncological field, these 3D models can be useful for in vitro production of human hematopoietic cells. Indeed, the HSCs transplantation, a widely used therapy for several hematological malignancies, presents two important limitations: an insufficient number of matching donors and the difficulty of obtaining enough cells [174]. Thus, expanding HSCs, obtained from donors, can be a suitable strategy to overcome these obstacles.…”
Section: D Models For Expanding Normal Hsc a Tool For Clinical Therapymentioning
confidence: 99%
“…Cultures in rotating wall vessel bioreactors and orbital shake flasks with intermittent shaking both resulted in an elevated multiplication of cells expressing the surface marker CD34 + —that labels hematopoietic stem and progenitor cells (HSPCs)—compared to static cultures 51, 52 . Studies on more complex dynamic 3D setups including a co-culture of lineage-negative UCB cells with bone marrow stroma cells in a hollow fibre continuous perfusion reactor, however, reported expansion rates similar to static 2D co-culture setups 53 or an enrichment of myeloid progenitors rather than of HSCs 54 . The bone marrow-on-a-chip by Torisawa et al .…”
Section: Introductionmentioning
confidence: 96%
“…Both these cell types lie in very close proximity to quiescent HSCs in vivo suggesting the potential involvement for flow on HSC development and function (Kumar and Geiger 2017). Only a handful of previous studies have investigated the effects of flow on hematopoietic-associated co-cultures within hollow fiber reactors (Davis et al 1996; Xue et al 2014). Both these studies showed success in expanding sub-purified Lineage negative and purified CD34 + cells from human umbilical cord blood in hollow fiber bioreactors directly co-cultured with MSCs and endothelial cells respectively, and supplemented with cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Both these studies showed success in expanding sub-purified Lineage negative and purified CD34 + cells from human umbilical cord blood in hollow fiber bioreactors directly co-cultured with MSCs and endothelial cells respectively, and supplemented with cytokines. Xue et al was able to demonstrate a 60-fold increase in CD34 + cell numbers and unaltered homing capacities through mice reconstitution studies (Xue et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation